The Role of Law Clinics and Legal Aid Center in Providing Legal Aid for Vulnerable Group: A Case of Africa, Indonesia, and Australia - Daniel Akintunde; Sutiani Choirunnisa; Christoper Bastiaan Fernando (Universitas Negeri Semarang, 2022)
Legal aid is a concept in response to the community's need for the adage